Model of Long-Term Improvement for the Efficiency of the Training Process in Greco-Roman Wrestling: Physiological, Psychological, and Technical Aspects, Individualization of Training - Krymov A.I. , (Theory and Practice of Physical Culture, 2025)
This article is dedicated to the study of long-term training methods for Greco-Roman wrestlers, focusing on the individualization of training and consideration of physiological, psychological, and technical-tactical parameters. The article presents a model of long-term improvement in the training process, taking into account the individual characteristics of athletes at different stages of their development. The stages of wrestlers' development from adolescence are examined, and methodologies adapted to anthropometric and psychophysiological characteristics are proposed. Particular attention is paid to a comprehensive approach that includes strength, endurance, and coordination development, injury prevention, and optimization of training loads considering the specifics of Greco-Roman wrestling. Coaches must consider each athlete's individual characteristics, such as their physical and psychological readiness level, to prevent injuries and burnout. Individualized training programs help improve preparation efficiency and develop technical-tactical skills crucial for successful competition performances. The proposed model of long-term improvement contributes to maintaining stable results at high-level competitions and ensuring the harmonious development of athletes in the long term.